When Accessibility Becomes Performance: Performativity as an Element and Carrier of Accessibility in Sign-Language-Interpreted Music - Tarantini, Angela Tiziana (Journal of Audiovisual Translation, 2023)
Accessibility is a key concept in audiovisual translation. In recent years, the importance of equal access not only to information, services, and media, but also to the arts has been gaining more attention. Accessibility provisions for popular music, however, have not been as comprehensive as for other types of music. In order to facilitate access to music for deaf signers, a generation of interpreter-performers started to embody nonverbal elements of the “text,” such as rhythm, pitch, tempo, etc., when translating a song into sign language. This practice, which is a form of audiovisual translation, is gaining momentum and has been the object of analysis in other disciplines (e.g., Musicology or Deaf Studies), but is under-investigated within Translation and Interpreting Studies. Working from studies in signed songs, from the work of Grant, and from Marinetti’s notion of translation as “performative rewriting”, I aim to show that performativity, intended as an action related to performance, but also with transformative potential, can become an element and a carrier of accessibility, and is at the core of these interpreting practices. The distinction between accessibility and access, however, must also be taken into account, and whether these practices actually facilitate access remains to be established by the deaf community. Lay summary Nowadays service providers pay more attention to the notion of accessibility and access, and not only to information and services, but also to the arts. More and more sign language interpreters translate songs and live concert in sign language to facilitate access for deaf people. They translate the lyrics of songs but also embody other elements of music in their interpretation, thus making music a visual form of performing art. Notions such as accessibility and access, however, are far from uncontroversial. Accessibility Studies scholar Greco has clarified the difference between the two. In this article I argue that performativity is an element and a carrier of accessibility. The idea of performativity is further elaborated working from Performance Philosophy, rather than Performance Theory. I further argue that, while sign-language-interpreted music is an accessibility provision, only deaf people can establish whether it actually facilitates access to music.